O docente administrador no estado do Piaui: profissionalidade e saberes da prática docente - Bezerra, Elaine Pontes (2019)
The business administration course is one of the most offered higher education courses in Brazil today, which generates a great demand for teaching administrators in Higher Education Institutions (HEIs). They enter their careers without a minimum preparation suitable for teaching, making it necessary for the HEIs and themselves to understand the aspects that lead to their pedagogical practice, especially regarding their professionalism and teaching knowledge. The study is linked to the Research Line Knowledge and Educational Practices. The thesis defended was that the teaching professors understand the importance of the professionality and teaching knowledge categories for their profession, being able to perform a pedagogical practice consistent with these categories and presented as general objective: Investigate, study and understand the degree of importance which the bachelors of administration professors of the public universities of the state of Piauí attribute to the categories of study of their pedagogical practice: professionality and teaching knowledge. The specific objectives were: 1) To ascertain the ideas that Bachelors of Business Administration professors of public universities of Piauí have about their pedagogical practice; 2) Find out how the administration teacher contributes through his pedagogical practice, to the development of the competences and skills established by the National Curriculum Guidelines (DCNs) of the Administration course, in the student. It is an exploratory, descriptive survey research, with quantitative and qualitative approaches. The research instrument used was a structured questionnaire, developed on the Google Docs platform, with closed questions arranged in five-point Likert scale and open questions. For the analysis of quantitative data we used descriptive statistics and qualitative data was Bardin content analysis. The participation of 51 professors of the administration courses of the public universities of the state of Piauí was obtained. The results allowed us to infer that the administration professors consider very important the aspects of teaching professionalism and knowledge of their pedagogical practice, highlighting the fact that they recognize that there are specificities for teaching professionalism; assume that the work context affects your professionalism; concern themselves with the student's professional education and admit the need to know how to transform information into knowledge in daily life. About the ideas that the researched teachers have about their teaching practice, the following were found mainly: to contribute to the professional and human formation of the student; commit to student learning; reconcile theory and practice. It was also found that the managing teacher contributes to the development of students' competences and skills, mainly through pedagogical practices that consider: the relationship theory and practice; the contextualization of pedagogical practices; teaching with emphasis on the student.